Electronically tunable MOSFET-based resistor used in a variable gain amplifier or filter - Tan, Wei Lin (2021)
We present a new design of an electronically tunable linear MOS resistor circuit that operates in the subthreshold saturation region, supported with mathematical derivations and simulation results using CSM0.13μm technology. For a given potential difference across the MOS resistor, its gate voltage will be automatically biased through feedback to provide the correct amount of current based on the desired resistance set through the bias current. In comparison with an existing design [1], the proposed design offers equal tunabilty with 36 less transistors for unidirectional current and 28 less transistors with one more bias current transistor for bidirectional current. A bias current ranging between 10nA to 100nA offers a tunable linear resistance between 20MΩ to 140MΩ.